Tafsir Sufistik Jawi (Corak Tafsir Kyai Sholeh Darat Dalam Kitab Tafsir Faid Al-Rahman) - Nur Baety Amalia (AQWAL Journal of Qur'an and Hadis Studies, 2023)
This paper discusses the Sufistic nuanced and Javanese language interpretation written using Arabic Pegon by Kyai Haji Sholeh Darat. The focus of the discussion is on Tafsir Faid Al Rahman. Kyai Sholeh Darat's interpretation has Isyārī elements. In this paper, there are three problem formulations that will be discussed by the author, namely first, how the method used in the book of interpretation of Faid Al-Rahman. Second, how is the locality aspect in the interpretation. Third, what are the examples of the Sufistic elements in this interpretation? This study uses a hermeneutic approach. The type of research is a type of library research or library research. In this paper it is concluded that Faid Al-Rahman's interpretation has a nuanced Sufistic characteristic written in the Javanese Pegon language using the tahlili method. This is inseparable from the social and cultural conditions inherent in the community around the mufassir. As for examples of interpretation, for example related to halal and unlawful food. Which interpretation has an outer and inner meaning.